Pediatric pressure injuries: does modifying a tool alter the risk assessment outcome?. (December 2013) - Leonard, Paul; Hill, Astrid; Moon, Kylie; Lima, Sally
<x xml:space="preserve">Abstract</x> The aim of this study was to determine whether assessing patient risk of developing pressure injuries in Pediatric Intensive Care (PICU) and Neonatal Units (NNU) using a modification of the Glamorgan Scale (mGS) would alter the risk identification when compared to the Glamorgan Scale (GS). Prospective data were collected from a convenience sample of patients admitted to PICU or NNU during a 2-month period. The patients' pressure injury risk score using both instruments was collected by observing patients, reviewing patient records, and clarifying information with bedside nurses. Chi square analysis was used to compare the risk category allocations. A total of 133 patients were assessed with complete data available for 112 (PICU = 68, NNU = 65). The total number of admissions during the data collection period was 202 in PICU and 100 in NNU. There was an extensive spread of patients allocated to the "High Risk" and "Very High Risk" categories in both units. Only one was in the lower "At Risk" category. There was little difference in allocated risk category between the mGS and the GS (p = 0.982). Only one patient was not allocated to the same risk category by both tools. In addition to identifying little difference in risk identification the mGS was found to be easier to complete. The mGS delivered the same risk rating as the GS when applied to patients in the PICU and NNU. It is not clear if a similar agreement exists in the general pediatric population. When modifying a validated tool for local use consideration should be given as to how those modifications might alter outcomes.